THE SPECIFIC OF PSYCHOSOCIAL WELL-BEING OF INTERNALLY DISPLACED PERSONS (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article is devoted to the problem of psychosocial well-being of internally displaced persons. The situation of forced internal migration conceals a large number of destructive influences on the psychosocial well-being of the individual. The process of adaptation of forced migrants is accompanied by high levels of stress and requires a large amount of psychological and social resources. In this regard, the research of psychosocial well-being of internally displaced persons is relevant to the scientific substantiation of psychosocial practice of assistance IDP.The purpose of the article is to reveal the peculiarities of the psychosocial well-being of internally displaced persons, which are based on the results of empirical research. The article presents the results of a theoretical and methodological analysis of the concept of psychosocial well-being of internally displaced persons. This concept is interpreted by the author as a multifactorial construct, which encompasses the individual psychological characteristics of internally displaced persons, their subjective attitude to the actual life situation, the nature of social interaction with others and economic factors of life activity. The results of empirical research aimed at identifying the characteristics of psychosocial well- being of internally displaced persons point to a reduced level of psychosocial well-being of internally displaced persons, reflected in the manifestations of the tendency to disadaptation. Characteristic features of internally displaced persons are the inability to establish close social contacts with others and emotional detachment and lowered sense of their value to society. The general emotional background of the IDP is at a reduced level and is characterized by tendencies towards negativism.
Keywords: psychosocial well-being, internally displaced persons, forced migration, social and psychological adaptation.